2015
DOI: 10.1074/jbc.m114.605543
|View full text |Cite
|
Sign up to set email alerts
|

The Guanine Nucleotide Exchange Factor (GEF) Asef2 Promotes Dendritic Spine Formation via Rac Activation and Spinophilin-dependent Targeting

Abstract: Background:The role of Rho family GEFs in dendritic spine formation is currently not well understood. Results: The Rho family GEF Asef2 promotes spine and synapse formation through activation of Rac and spinophilin-mediated localization to spines. Conclusion: Asef2 is a critical regulator of spines and synapses. Significance: Asef2-spinophilin signaling is an important, new mechanism for inducing spine and synapse development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 78 publications
1
23
1
Order By: Relevance
“…Spinophilin modulates dendritic spine density and regulates LTD [17, 3739]. Spinophilin is known to associate with and modulate the function of multiple synaptic proteins [19, 26, 3942].…”
Section: Discussionmentioning
confidence: 99%
“…Spinophilin modulates dendritic spine density and regulates LTD [17, 3739]. Spinophilin is known to associate with and modulate the function of multiple synaptic proteins [19, 26, 3942].…”
Section: Discussionmentioning
confidence: 99%
“…A closely related homolog of Ephexin5, Ephexin1 displays GEF specificity that is regulated by its phosphorylation state. Similarly to Ephexin5, Ephexin1 has been shown to target RhoA, but is also capable of activating Cdc42 and Rac1 (Shamah et al, 2001; Sahin et al, 2005), both of which enhance spine density (Tashiro et al, 2000; Wiens et al, 2005; Wegner et al, 2008; Kim et al, 2013; Ueda et al, 2013; Dhar et al, 2014; Raynaud et al, 2014; Evans et al, 2015; Jaudon et al, 2015; Kim et al, 2015; Valdez et al, 2016). Phosphorylation of Ephexin1 by Src kinase, however, causes a shift in Ephexin1 affinity away from Rac1 and Cdc42 towards RhoA, a switch which mediates EphA4-dependent growth cone collapse through RhoA activation (Shamah et al, 2001; Sahin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several small GTPases have been characterized as enhancers of spine density, especially Cdc42 (Tashiro et al, 2000; Wegner et al, 2008; Kim et al, 2013; Jaudon et al, 2015) and Rac1 (Tashiro et al, 2000; Penzes et al, 2001; Penzes et al, 2003; Tolias et al, 2007; Bacon et al, 2013; Ueda et al, 2013; Dhar et al, 2014; Raynaud et al, 2014; Evans et al, 2015; Jaudon et al, 2015; Kim et al, 2015; Valdez et al, 2016); others have been shown to inhibit spine density, in particular Ras (Yang et al, 2013; Lee et al, 2016) and RhoA (Tashiro et al, 2000; Margolis et al, 2010; Alder et al, 2013; Kim et al, 2015). Furthermore, modulators of activity for Ras (Pham and Rotin, 2001), Cdc42 (Hayakawa et al, 2008; Yamaguchi et al, 2008), and RhoA (Margolis et al, 2010; Lin et al, 2011; Papadimitriou et al, 2012) have been shown to be degraded by the proteasome, as well as Rac1 (Torrino et al, 2011; Zhao et al, 2013) and RhoA themselves (Wang et al, 2003; Cheng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a remarkable in vivo study in non-heat-stressed C. elegans, stimulation of the worms' thermo-sensory neurons activated HSF1 in distal tissues (the pharyngeal muscles) (Tatum et al 2015). Rho family GTPases like Rac 1 also activate HSF1 (Han et al 2001;Gungor et al 2014) and play a role in formation of the synaptic spine cytoskeleton (Evans et al 2015). Glycogen synthase kinase-3 (GSK3) inhibition promotes activation of HSF1 by AKT activation (Bijur and Jope 2000), and is associated with synaptic functional integrity and improved cognitive ability (King et al 2014).…”
Section: Pathways Of Hsf1 Activationmentioning
confidence: 93%